Photoluminescence and quantum yield behaviour of vanadium doped Zn2SiO4 phosphors facilely synthesized by sol-gel method. (17th February 2023) - Diana, P; Sebastian, S; Saravanakumar, S; Chidhambaram, N; Shkir, Mohd; Alqahtani, Aminah Nasser
Abstract: Vanadium-doped Zinc Silicate (Zn2 SiO4 ) phosphors were synthesized through the sol-gel method. Structural, morphological and optical techniques were used to investigate the effects of vanadium incorporation on their structure, morphology, and optical behaviour. We reported that vanadium incorporation in Zn2 SiO4 phosphors significantly modifies their crystallinity, morphology, and photoluminescence properties. When vanadium is added to Zn2 SiO4 phosphors, the energy band gap (Eg ) changes from 5.29 to 2.34 eV. Vanadium dopants generate imperfections in Zn2 SiO4 phosphors, the leading cause of their emissions in visible regions and quantum yield. Quantum yield is estimated at 7.06% for Zn2−x Vx SiO4 (x = 0.08) phosphor. The luminescence decay lifetime of the prominent emissions of vanadium-doped Zn2 SiO4 was measured using a double exponential fitting technique, and the average lifetime is 11.7 ns.